(untitled) (International Journal of Environmental Sciences, 2025)
The primary goals of this study are to design, model, and analyze the structural characteristics of automobile wheel rims made of various materials, such as magnesium alloy (AM60B) and aluminium alloys (Al-7068, AlSi7Mg0.3). The primary objective is to evaluate and compare the structural performance of three different wheel rims under identical stress and boundary conditions using ANSYS 2025 R1Workbench. Each design is tested for total deformation and equivalent (Von-Mises) stresses under radial loads, internal pressure, and rotational velocities comparable to a vehicle speed of 160 km/h. The 3D CAD models were made with SpaceClaim, and the strength and durability characteristics of the materials were assessed using finite element analysis (FEA). Simulation results showed that Design 3 with AlSi7Mg0.3 outperformed the other analyzed configurations, exhibiting the least amount of total deformation (0.153 mm) and Von-Mises stress (13.49 MPa). Al-7068 followed closely behind, but AM60B, while being lighter, deformed more under stress. The project’s conclusions indicate that aluminium alloys, namely AlSi7Mg0.3, provide the ideal balance of strength, weight, and deformation resistance for car wheel rims, which qualifies them for enhanced performance and fuel efficiency. This study provides valuable insights into material selection and design optimization for safer and more efficient automotive components.